Performance appraisal purposes: the predictors of employee engagement / Abdullateef Ameen and Mohd Nazri Baharom - Ameen, Abdullateef; Baharom, Mohd Nazri (2019)
Given that employee engagement is germane to the achievement of organisational objectives, and that productivity and performances of organizations are enhanced through the instrumentality of engaged workforce, many studies have examined several predictors of employee engagement, but the most important predictor of employee engagement is the performance appraisal system, because, it is a significant factor that can enable organizations achieve employee efficiency. However, little has been done concerning the effect of performance appraisal purposes (measured with feedback, training, job promotion, recognition and financial reward) on employee engagement. Therefore, to solidify the findings of the existing literature on performance appraisal purposes and employee engagement connection, and to enrich the existing body of knowledge in the employee engagement research field, this research proposes a conceptual model, signifying a positive connection between performance appraisal purposes and employee engagement. It draws upon a comprehensive review of extant literature, this paper advocates that performance appraisal purposes have a positive effect on employee engagement, and that organizations require to recognise how diverse workforces are affected by different factors of performance appraisal purposes, such as, training, job promotion, feedback, recognition and financial reward, as this would facilitate accomplishment of strategic outcomes, as well as effectiveness and engagement. The proposed model is considered logical and empirical, and therefore can be tested further through collection and analysis of relevant data by future researchers.